Effects of chamomile essence aromatherapy on episiotomy pain of primiparous women - Pazandeh, F; Savadzadeh, Sh; Mojab, F; Alavi Majd, H (Advances in Nursing & Midwifery, 2009)
Background Pain is one of the most common complaints, putting the balance and health of patients at risk. Episiotomy is a frequent surgical procedure causing pain. Pharmacological and non-pharmacological methods are used today for pain relief. Purpose This double-blind clinical trial was conducted to determine the effects of aromatherapy with chamomile essence on episiotomy pain in primiparous women referring to Shaheed Norani Hospital at Talesh town in 2007. Methods 88 pregnant women undergoing episiotomy were selected by convenience sampling method and divided into 2 experimental and control groups. The experimental group was given sitz bath twice a day with chamomile essence while the other group used the same procedure with placebo. Both groups were taught pain severity assessment with a 10-point scale. The severity was assessed and documented in both groups on the 1st, 7th, and 14th days. A questionnaire, a health facility assessment form, a visual scale for pain and an analgesic consumption sheet were used for data collection. Content validity and inter-rater reliability were used for the tools. Results The severities of pain in the experimental and control groups on the 7th and 14th days were [2.20±0.79, 2.30±0.82] and [0.48±0.59, 0.73±0.66] respectively with no significant difference. Conclusion It seems that chamomile essence have no effect on the relief of episiotomy pain. Further studies in this regard are warranted. Keywords: Episiotomy pain, Chamomile essence, Aromatherapy.